An Approach Toward Replacing Vanadium: A Single Organic Molecule for the Anode and Cathode of an Aqueous Redox‐Flow Battery. Issue 2 (7th February 2017) - Janoschka, Tobias; Friebe, Christian; Hager, Martin D.; Martin, Norbert; Schubert, Ulrich S.
Abstract: By combining a viologen unit and a 2, 2, 6, 6‐tetramethylpiperidin‐1‐oxyl (TEMPO) radical in one single combi‐molecule, an artificial bipolar redox‐active material, 1‐(4‐(((1‐oxyl‐2, 2, 6, 6‐tetramethylpiperidin‐4‐yl)oxy)carbonyl)benzyl)‐1′‐methyl‐[4, 4′‐bipyridine]‐1, 1′‐diium‐chloride (VIOTEMP ), was created that can serve as both the anode (−0.49 V) and cathode (0.67 V vs. Ag/AgCl) in a water‐based redox‐flow battery. While it mimics the redox states of flow battery metals like vanadium, the novel aqueous electrolyte does not require strongly acidic media and is best operated at pH 4. The electrochemical properties ofVIOTEMP were investigated by using cyclic voltammetry, rotating disc electrode experiments, and spectroelectrochemical methods. A redox‐flow battery was built and the suitability of the material for both electrodes was demonstrated through a polarity‐inversion experiment. Thus, an organic aqueous electrolyte system being safe in case of cross contamination is presented. Abstract : Toward replacing vanadium : By combining a viologen unit and a TEMPO radical in a single molecule, a bipolar, redox‐active material is created that can serve as both the anode and cathode of a water‐based redox‐flow battery (RFB). It mimics the redox states of vanadium salts and can, therefore, simplify the operation of organic RFBs. The material is electrochemically investigated and a test RFB cell is built.